The Impact of the COVID-19 Pandemic and Socioeconomic Deprivation on Admissions to the Emergency Department for Psychiatric Illness: An Observational Study in a Province of Southern Italy - Massimo Giotta; Francesco Addabbo; Antonia Mincuzzi; Nicola Bartolomeo (Life, 2023)
The restriction measures adopted to limit population movement in order to contain the COVID-19 pandemic contributed to a global public health system crisis. This retrospective study aimed at identifying changes in psychiatric admissions to Accident and Emergency Departments (A&Es) in a province in southern Italy during the first two years of the pandemic and was characterized by two different restriction levels (phases 2 and 3) compared to the pre-pandemic period (phase 1). We also investigated the role of socioeconomic deprivation (DI) on psychiatric admissions. The total number of patients admitted to the A&Es was 291,310. The incidence of admission for a psychiatric disorder (IPd) was 4.9 per 1000 admissions, with a significant younger median age of 42 [IQR 33–56] compared to non-psychiatric patients (54 [35–73]). The type of admission and type of discharge were factors related to the psychiatric admission to A&E, and their relationship was modified by the pandemic. In the first year of the pandemic, patients with psychomotor agitation increased compared to the pre-pandemic period (72.5% vs. 62.3%). In the period preceding the spread of SARS-CoV-2, the IPd was equal to 3.33 ± 0.19; after the pandemic started, there was an increase in the IPd: 4.74 ± 0.32 for phase 2 and 3.68 ± 0.25 for phase 3. The IPd was higher for psychiatric admissions from areas with a very low DI compared to areas with a low DI; however, during phase 2, this difference was reduced. In conclusion, an increase in admissions for psychiatric disease was observed during the initial spread of SARS-CoV-2. Patients who lived in the most deprived municipalities generally came to the A&Es less than others, probably because the patients and their families had less awareness of their mental health. Therefore, public health policies to address these issues are needed to reduce the pandemic’s impact on these conditions.